MANGROVE IN THE COASTAL ZONE OF LAMPUNG BAY PROVINCE OF LAMPUNG: A PRELIMINARY STUDY - Pramudji, - (Marine Research in Indonesia, 2007)
Study on mangrove forest in the coastal zone of Lampung Bay, Province of Lampung was carried out on March 12 â 30, 2007. The data was collected from 8 stations, (Pidada Bay, Limbungan, Puhawang Kecil Island, Kalangan, Klagian Island, Kapuran, Ringgung, and Hurun Bay) based on the transect method. The result showed that the mangrove in the coastal zone of Lampung Bay was dominated by Rhizophora apiculata. The floristic composition of mangrove in this area consisted of 31 species. Recently, the extent of mangrove in the coastal zone of Lampung Bay was decreasing due to conversion of mangrove into human settlement, fishpond, road, and uncontrolled mangrove exploitation. This situation leads to the depletion of the living organisms which inhabit this area.